Influence of Temperature Changes on the Performance Characteristics of Some Selected Semiconductor PN-Junction Diodes - Moses, Odepeli; Ohajianya, Anthony; Ndukwe, Israel (Journal of Electronics and Electrical Engineering, 2025)
Temperature changes can significantly impact the performance characteristics of semiconductor diodes. The key effects of an increase in temperature on the intrinsic properties of the semiconductor diodes include an increase in charge carrier concentration, a decrease in charge carrier mobility, and a decrease in bandgap. This research was carried out to study and generate data on the effect of temperature changes on the performance characteristics of some selected semiconductor pn-junction diodes. The pn-junction diodes studied include IN5400, IN5401, IN5402, and IN5404 diodes. These diodes were in turn placed in a test circuit, and a heater was used to increase their ambient temperature from 25 °C to 200 °C. The voltage was measured and the current, static resistance, and dissipated power were determined for each of the diodes as the temperature varied. The results show that for the forward-biased diodes, the diode voltage generally decreased with an increase in temperature while the current increased with an increase in temperature. The forward static resistance and dissipated power generally decreased with an increase in temperature. The effect of ambient temperature on the reverse-biased diode voltage and current was negligible till the temperature of about 150 °C. We recommend that designers and manufacturers of electronic devices should study the data on the effect of temperature on any electronic component before such a component is used irrespective of the power capacity of the component. This is because this research has shown that even low-power electronic components can be affected by ambient heat generated from other components.